SOSIALISASI DAN PENDAMPINGAN DAMPAK PENGGUNAAN DAGDET PADA MASYARAKAT DI DESA BOYOLANGU - Ria, Ria Fajrin Rizqy Ana; Nourma Oktaviarini (Kanigara, 2022)
The use of gadgets that do not meet the needs of children will adversely affect their physical and behavioral development. The problems that arise with partners are that many children use gadgets without knowing the time limit and the lack of supervision from parents in using gadgets. Therefore, socialization and assistance on the impact of using gadgets on parents need to be carried out, so it is hoped that gadgets are only used for positive things for children. This community service activity was carried out in Boyolangu Village. The objectives of this community service are (1) to provide socialization to parents about the impact of using gadgets, (2) to provide assistance to parents to lock applications with negative content and provide guidance, direction, attention to their relatives, especially in the use of gadgets. Implementation of the activities carried out by the method of lectures, question and answer, discussion, and direct practice. Media delivery is in the form of pictures and videos about the negative impact of gadgets, as well as application locking videos. The implementation stages consist of the observation stage, program preparation, implementation, monitoring, and evaluation. Activities can be carried out properly. The results of this service activity are parents are able to understand the positive and negative impacts of continuous use of gadgets, parents can limit their children to play gadgets, and parents can lock applications that contain negative content and can restrict children from downloading games.